Biodiversity of the Microalgal Population in Chettikulam Pond of Tenkasi District, Tamil Nadu, India - K. , Arulmeha Ponradha; Nirmala, C.B. (International Journal of Psychosocial Rehabilitation, 2020)
The number of natural ponds of Tamil Nadu is declining at a phenomenal rate. Consequently, there is not only water scarcity but also a loss of biodiversity of microalgae. The record of phytoplankton is essential in order to know the endangering algal species in these freshwater bodies. Chettikulam pond of Tenkasi Taluk was chosen to monitor the microalgal population as it is subjected to continuous exploitation by human beings. Totally 107 species were recorded from four main classes namely, Chlorophyceae, Bacillariophyceae, Euglenophyceae and Cyanophyceae. The class Chlorophyceae was dominant with 53 species followed by Bacillariophyceae with 31 species, Euglenophyceae with 6 species and Cyanophyceae with 17 species. Diversity indices calculated from the results show that the pond has a moderate level of diversity and Palmer index indicates that the ponds are polluted by organic compounds.